ANALISIS RISIKO PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS DAN PENGEMBALIAN PEMBIAYAAN NASABAH PADA BPRS BUMI RINJANI PROBOLINGGO periode tahun 2011-2016 - Wiwik Fitria Ningsih (RELASI : JURNAL EKONOMI, 2017)
This study aims to determine the relationship of Musyarakah financing risk to profitability and the risk relationship of Musyarakah financing to the rate of return of financing at BPRS Bumi Rinjani Probolinggo in 2011-2016. Data collection use documentation method. The data are annual financial report 2011-2016. Based on the data analysis, it is known that in 2013, 2015 and 2016 NPF Musyarakah increased and ROA decreased, so it can be interpreted that if problematic financing at BPRS Bumi Rinjani Probolinggo high it will reduce the profit. But by 2014 when NPF declines, ROA declines. This means that the NPF condition in a period does not directly give a decrease in profit in the same period. In 2015 and 2016 there is an increase in Musyarakah NPF, so it is concluded that the quality of BPRS Financing is getting worse. Similarly, the rate of return of musyarakah financing that occurred at the BPRS Bumi Rinjani Probolinggo decreased, which means the returns obtained from a fund or capital invested in an investment decreased.